Formação continuada dos atores do sistema de garantia de direitos da criança e do adolescente: uma análise com base nas deliberações das conferências nacionais (2007-2020) - Oliveira, Sirlei de (Universidade do Vale do Rio dos Sinos, 2025)
This thesis aims to study the perspectives of continuing education for actors in the Children and Sistema de Garantia dos Direitos das Crianças e Adolescentes (SGDCA) presented throughout the Conferências Nacionais dos Direitos das Crianças e dos Adolescentes (CNDCA). The research problem was developed based on the researcher's professional and academic experience, namely: What are the perspectives of continuing education for actors in the Children and Adolescents' Rights Guarantee System (SGDCA) observed in the Deliberations of the National Conferences on the Rights of Children and Adolescents? How are they configured in relation to the different sociopolitical contexts in which the Conferences were held? The empirical field is the Deliberations of the Conferences, which are studied through documentary analysis, with the initial delimitation being the year 2007 – the time of the first CNDCA, held after the creation of the Conselho Nacional dos Direitos da Criança e do Adolescente (CONANDA) and the publication of Resolutions No. 112 and 113 of 2006 – and the final delimitation being the year 2020, when the last Conference took place with the Deliberations available up to the time of the research. The data were processed through discursive textual analysis (Moraes 2007). As a result, the following thesis was formulated: Continuous training/qualification of the SGDCA actors is foreseen in all the Deliberations analyzed in this research, with the convergent point being suggestions for it to be provided in intersectoral and interdisciplinary actions. The documentation analyzed allows us to conclude that at the CONANDA National Conferences it was considered that through continuous training/qualification, SGDCA actors will have the possibility of an interdisciplinary perspective and the ability to articulate different public policies to offer adequate and effective responses in the defense of the rights of children and adolescents.
Keywords: Sistema de Garantia de Direitos da Criança e do Adolescente; Formação continuada; Conferência Nacional; Child and Adolescent Rights Guarantee System; Continuing education; National Conference; ACCNPQ::Ciências Humanas::Educação